ANALISIS PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA PELAJARAN SOSIOLOGI KELAS X IIS SMA NEGERI 1 TELUK PAKEDAI - Merry Melinda; Amrazi Zakso; Izhar Salim (Universitas Tanjungpura, 2019)
AbstractThe title of this thesis: The Analysis of the Implementation of Problem Based Learning Model on Sociology Subject in the Class X IIS SMA Negeri 1 Teluk Pakedai. This research aimed to figure out 1. The way of the teacher in explaining lesson objectives. 2. The way of the teacher in helping students to define and to organize tasks. 3. The way of the teacher in encouraging students to collect information. 4. The way of the teacher in helping students to plan and to prepare creations. 5. The way of the teacher in helping students to do reflection and evacuation. This research used the qualitative approach with descriptive method. The techniques of data collection in this research were observation, interview, and documentation stud. The tools of data collection were observation guide, interview guide, note books, and archives. The informants in this research were teachers, students, and the school principal. The result of this research showed that the role of the Sociology teacher in implementing the Problem Based Learning model was good enough and there was an increase in every time the learning model was applied.Keywords: Implementation, Problem Based Learning, Sociology Subject